Hepatitis B core antigen is a potent inductor of interleukin-18 in peripheral blood mononuclear cells of healthy controls and patients with hepatitis B infection - Manigold, Tobias; Böcker, Ulrich; Chen, Jingsan; Gundt, Jutta; Traber, Petra Sieglinde; Singer, Manfred V.; Rossol, Siegbert (Journal of medical virology, 2003)
Clearance of hepatitis B virus infection (HBV) infection implies a polyclonal vigorous T-helper 1 (Th1) and cytotoxic T-lymphocyte (CTL) response. Interleukin-18 (IL-18), a monokine that shares functional abilities with IL-12, is a potent inductor of interferon-γ (IFN-γ) by Th1 and natural killer (NK) cells. However, the role and regulation in HBV infection of IFN-γ have not been defined. This study therefore sought to determine hepatitis B core antigen (HBcAg)-mediated regulation of IL-18 production in peripheral blood mononuclear cells (PBMCs) from healthy controls (HC) and patients with chronic hepatitis B (CHB) or acute hepatitis B (AHB); 31 HC, 27 patients with CHB and 8 patients with AHB infection were included in the study. HBcAg-mediated induction of IL-18 was determined by quantitative reverse transcription-polymerase chain reaction (RT-PCR) and specific enzyme-linked immunosorbent assay (ELISA). HBcAg induced IL-18 gene transcription and dose-dependent secretion of mature IL-18 protein in HC, CHB, and AHB. HBcAg-dependent IL-18 levels were abrogated by inhibition of Caspase-1, but not by blockade of CD40-CD154 interaction. Serum levels of IFN-γ correlated inversely with viremia in patients with CHB (ρ = − 0.54, P < 0.05), but not with serum levels of IL-12 or IL-18. Interestingly, in PBMCs of HBeAg-negative patients, HBcAg induced significantly higher amounts of IL-18 than in those of HBeAg-positive patients. A variant, lacking the histone-like arginine-rich domain, did not induce IL-18 in either HC or CHB in vitro. Taken together, these results indicate that HBcAg induces IL-18 secretion by induction of Caspase-1. Differential regulation in HBeAg-negative and positive patients suggests an important role of IL-18 in CHB infection. J. Med. Virol. 71:31-40, 2003. © 2003 Wiley-Liss, Inc.